Budget impact analysis of the incorporating of biosimilars in a cancer institute of a philanthropic hospital - Maria Luísa BRODT-LEMES; Diana Saiara BRUSCATO; Douglas Silva MADRUGA; Joice SMANIOTTO; Julia Roberta SAGGIORATO-LUBIAN; Letícia Tramontina DE-VILLA; Suhélen CAON; Thamyrys Bessa SILVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: Global healthcare costs continue to rise annually, and this is a major challenge given the scarce resources and growing prices of innovative drugs. An interesting alternative for reducing costs is the use of biosimilars. This study aimed to assess the financial impact of introducing biosimilars of the drugs adalimumab, rituximab and trastuzumab in a Cancer Institute of a Philanthropic Hospital in the South of the country. Method: This is a retrospective, descriptive study in which a budgetary impact analysis was used to assess the savings generated by the biosimilars standardized at the institution between January 2020 and December 2023. Information on the average cost and monthly consumption of the three biosimilars: adalimumab, rituximab and trastuzumab was used to assess the financial impact. The economic analysis was carried out using the difference between the cost of the biosimilar and the cost of the reference drug, multiplied by annual consumption. Results: It was evidenced during the study period the cost reduction after switching the reference biological with the corresponding biosimilar was R$ 1.540.701,18 (U$ 279.077,14) for adalimumab, R$ 129.824,93 (U$ 23.516,03) for rituximab and R$ 1.604.319,28 (U$ 290.600,70) for trastuzumab. The analysis identified that the standardization of biosimilars at the institution resulted in a global economy of R$ 3.274.845,39 (U$ 593.193,87). Conclusion: The use of biosimilars proved to be a more economical option when compared to the use of the reference biological. In conclusion, the use of biosimilars allows for a considerable reduction in overall treatment costs, especially in the case of innovative and expensive therapies. Therefore, the incorporation of biosimilars is considered an interesting option in the search for the sustainability of health systems.